Power - Moten, Abdul Rashid (Oxford University Press, 2014)
Power, defined as the ability to make someone do something which he or she otherwise would not do, plays a central role in Islam. Power is essential to maintain order and progress in the society (Qurʾān 4:59, 43:32). The Qurʾān states categorically that power can be exercised for the good of a person or the society, just as it can be used to create and perpetuate injustice, oppression, and stagnation (6:123, 20:24, 27:34, 33:67, 34:34, 43:23–24, etc.). The Qurʾān abhors the abuse of power and enjoins the believers to use power for the good of the self and the society. Power could be used as an end in itself, just as it can be used as a means to an end. In Islam, the emphasis has always been to use power as a means to earn the pleasure of Almighty Allāh. Power must not be used for aggression.